Nuclear receptors CAR and PXR as cardiometabolic regulators - Janne Hukkanen; Jenni Küblbeck; Jukka Hakkola; Jaana Rysä (Pharmacological Research)
The constitutive androstane receptor (CAR) and pregnane X receptor (PXR) were initially described as xenobiotic sensors, but an increasing number of studies have linked their activity to other important physiological processes including glucose and lipid metabolism, implying an expanded role as metabolic sensors. CAR and PXR are nuclear receptors, which share similarities in expression, ligand-specificity, and mechanism of transcriptional regulation but they have their distinct features as well. Together, they regulate a wide array of target genes, whose functions range from elimination of xenobiotics to energy metabolism. Both CAR and PXR have large ligand binding pockets, and especially the PXR pocket is flexible for structurally different chemicals. Consequently, CAR and PXR could have a role in mediating the harmful metabolic effects of drugs and environmental chemicals. Current knowledge supports a role for PXR in the regulation of lipid and cholesterol metabolism. The actions seem to be mostly unfavorable, since the activation of PXR has been shown to promote hepatic lipogenesis and hyperlipidemia, increase plasma cholesterol and impair hepatic LDL uptake. PXR and PXR-regulated circulating 4β-hydroxycholesterol may also influence blood pressure regulation. CAR, in contrast, tends to exert beneficial effects on lipid and glucose homeostasis, since CAR activation has been shown to reduce serum triglyceride and cholesterol levels and have anti-atherogenic properties. Here we review current knowledge on CAR and PXR as regulators of cardiometabolic functions, including glucose and lipid homeostasis, blood pressure regulation and atherosclerosis.